Disaster preparedness: A concept analysis and its application to the intensive care unit. Issue 2 (March 2022) - Sellers, David; Crilly, Julia; Ranse, Jamie
Abstract: Objectives: The aim of the study is to understand the concept of disaster preparedness in relation to the intensive care unit through the review and critique of the peer-reviewed literature. Review method used: Rodgers' method of evolutionary concept analysis was used in the study. Data sources: Healthcare databases included in the review were Cumulative Index to Nursing and Allied Health Literature, Public MEDLINE, Scopus, and ProQuest. Review methods: Electronic data bases were searched using terms such as "intensive care unit" OR "critical care" AND prep∗ OR readiness OR plan∗ AND disaster∗ OR "mass casualty incidents" OR "natural disaster" OR "disaster planning" NOT paed∗ OR ped∗ OR neonat∗. Peer-reviewed articles published in English between January 2000 and April 2020 that focused on intensive care unit disaster preparedness or included intensive care unit disaster preparedness as part of a facility-wide strategy were included in the analysis. Results: Eighteen articles were included in the concept analysis. Fourteen different terms were used to describe disaster preparedness in intensive care. Space, physical resources, and human resources were attributes that relied on each other and were required in sufficient quantities to generate an adequate response to patient surges from disasters. When one attribute is extended beyond normal operational capacities, the effectiveness and capacity of the other attributes will likely be limited. Conclusion: This concept analysis has shown the varied language used when referring to disaster preparedness relating to the intensive care unit within the research literature. Attributes including space, physical resources, and human resources were all found to be integral to a disaster response. Future research into what is required of these attributes to generate an all-hazards approach in disaster preparedness in intensive care units will contribute to optimising standards of care.